Sorption-enhanced steam reforming of ethanol for hydrogen production - Avendaño Cañizalez, Roger Orlando (2020)
In last years, sorption-enhanced steam reforming of ethanol (SESRE) has become an interesting alternative for the industry, since it offers high H2 purity with a simpler and smaller system. In this study CaO derived materials were synthesized to improve multicyclic CO2 sorption-desorption stability. A dispersant and inert phase (Ca12All4O33) was incorporated into CaO structure. The effects of CaO:Ca12Al14O33 ratio on the characteristics of the new absorbents and on their performance in sorption-enhanced steam reforming of ethanol were analyzed. The results obtained indicate that the absorbent 85% CaO – 15% Ca12Al14O33 had significantly improved cyclic reaction stability. Additionally, it was proved that with this adsorbent CO purity on wet basis was lower than 2 %, making it possible to attain in only one reaction stage the CO purity obtained after de WGS reactor.